الحقوق الشرعية للجاني في جرائم الحدود في مرحلة التنفيذ: دراسة تأصيلية تطبيقية على واقع عمل محاكم المملكة العربية السعودية - التليدي، سلمان بن صالح بن يحيى (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2022)
في هذا البحث جمع لجملة من حقوق الجاني في الشريعة الإسلامية في جرائم الحدود في مرحلة تنفيذ الحد، وقمت بدراستها من ناحية تأصـيلية مع إدراج تطبيقات لعمل المحاكم في المملكة العربية السعودية في كل مسألة أجد لها تطبيقا في مدونات أحكام ومبادئ المحاكم الجزائية المنشورة من وزارة العدل بالسعودية إن وجدت لها تطبيقا فيها، وقد انتهت هذه الدراسة المتواضعة إلى تقرير عدة حقوق للجناة في جرائم الحدود في مرحلة التنفيذ كفلتها لهم الشريعة الإسلامية؛ ما بين حق متفق عليه بين الفقهاء، أو مرجح مختار من بين أقوالهم منها: لزوم وسطية السوط، ووسطية الضرب، واتقاء المقاتل أثناء الجلد، وتقرير تأخير تنفيذ الحد بسبب المرض أو الحمل أو لأجل حر وبرد شديدين، وتداخل الحدود إذا تكرر موجب الحد قبل إقامة الحد، كما تعرض البحث لنازلة تخدير الجاني حال تنفيذ الحد، وما فيها من اختلاف الفقهاء المعاصرين بين مانع ومجيز بحسب نوع العقوبة الحدية، وقد انتهيت فيه إلى التوصـية بجمع حقوق الواردة في الشريعة الإسلامية للجاني في كافة الجرائم سواء الحدية أو غيرها، وفي كافة مراحل النظر القضائي. This research includes a collection of the legitimate rights of the offender in the Islamic Sharia especially in the prescribed crimes during execution. The researcher has investigated these rights from an originating perspective as well as inserting some applications of work within the courts of Saudi Arabia. Whenever the researcher finds an application of any case enrolled in the codes of judgements and principles of magistrates' courts and announced by the Saudi ministry of justice, he demonstrates it. The research has concluded with the most important findings. For instance, the Islamic Sharia has advocated the rights of the offenders in the prescribed crimes during the period of execution. Those rights vary in between approved, agreed or preponderant rights selected from the sayings of the jurists such as the requirement of a median whip, median lashing, being cautious when whipping a warrior, deciding to delay whipping because of illness, pregnancy, extreme cold or heat. In addition, the prescribed penalties overlap when the requisite of the penalty is repeated before its execution. Moreover, the research handles the issue of anesthetizing the offender while executing the penalty and the involved disagreement in between the contemporary jurists who are divided into two groups; the first does not allow whereas the other agrees in accordance with the type of penalty. Finally, the researcher recommends all the rights contained in the Islamic Sharia and prescribed for the offender in all crimes whether they are prescribed or else and in all the phases of judicial reviewing.
Keywords: أصول الفقة -- الحقوق الشرعية -- الجرائم الجنائية -- المحاكم السعودية -- حقوق الجناة -- المعاملات الإسلامية